4.1957   2y(x)y′′(x) = 6y′(x)2 + (1 − 3y(x)2)y(x)2

ODE

2y(x)y′′(x) = 6y′(x)2 + (1− 3y(x)2) y(x)2

ODE Classification

[[_2nd_order, _missing_x], [_2nd_order, _reducible, _mu_xy]]

Book solution method
TO DO

Mathematica
cpu = 1.27632 (sec), leaf count = 217

{{                                        }  {                                      }  {                                        }  {                                       } }
                      2ie12i(c2+x)                                 2ie12i(c2+x)                                   2ie12i(c2+x)                                  2ie12i(c2+x)
   y(x) → − ∘----i(c2+x)---2i(c2+x)----------  , y(x) → ∘-----i(c2+x)---2i(c2+x)----------  ,  y(x) → − ∘-----------2i(c2+x)-----i(c2+x)---- ,  y(x ) → ∘----------2i(c2+x)----i(c2+x)---
             − 12e     + e      + 16c1 + 36            − 12e      + e      + 16c1 + 36              4(4c1 + 9)e      − 12e     + 1             4 (4c1 + 9)e      − 12e     + 1

Maple
cpu = 0.041 (sec), leaf count = 25

{                                  2    }
  1+-( C1-sin-(x)-+-C2-cos(x)−-3)(y(x))-= 0
                (y (x ))2

Mathematica raw input

DSolve[2*y[x]*y''[x] == y[x]^2*(1 - 3*y[x]^2) + 6*y'[x]^2,y[x],x]

Mathematica raw output

{{y[x] -> ((-2*I)*E^((I/2)*(x + C[2])))/Sqrt[36 - 12*E^(I*(x + C[2])) + E^((2*I)
*(x + C[2])) + 16*C[1]]}, {y[x] -> ((2*I)*E^((I/2)*(x + C[2])))/Sqrt[36 - 12*E^(
I*(x + C[2])) + E^((2*I)*(x + C[2])) + 16*C[1]]}, {y[x] -> ((-2*I)*E^((I/2)*(x +
 C[2])))/Sqrt[1 - 12*E^(I*(x + C[2])) + 4*E^((2*I)*(x + C[2]))*(9 + 4*C[1])]}, {
y[x] -> ((2*I)*E^((I/2)*(x + C[2])))/Sqrt[1 - 12*E^(I*(x + C[2])) + 4*E^((2*I)*(
x + C[2]))*(9 + 4*C[1])]}}

Maple raw input

dsolve(2*y(x)*diff(diff(y(x),x),x) = 6*diff(y(x),x)^2+(1-3*y(x)^2)*y(x)^2, y(x),'implicit')

Maple raw output

(1+(_C1*sin(x)+_C2*cos(x)-3)*y(x)^2)/y(x)^2 = 0